Analysis Income of Closed House Broiler Farm On Non-Partnership Model (Case Study of CV. Sari Mulya in Tunjuk Village, Tabanan) - P.K.P., Wulansari; Sukanata, I W.; Suasta, I M. (Jurnal Peternakan Tropika, 2018)
There are two systems in broiler farm those are opened house and closed house. This study aims was to find out the income of closed house broiler farmat non-partnership farming model. It was conducted at CV. Sari Mulya Tunjuk VillageTabanan Regency, from March to May with data for 7 production period. Data obtained consist of primary and secondary data. The secondary data was the performance data at the first to the sixth periods, where as the primary data was the data from the following period (the 7 th period). The variables observed wereeconomic consisted of investment and production cost, revenue, income, R/C ratio and break even point (BEP). The data obtained was analyzed descriptive and quantitatively. The results showed that of investment cost is Rp 687.825.000, production cost is Rp 374.674.071/period, farmer's income is Rp 70.241.378, with an R/C ratio of 1.19. This effort reached BEP at 4.063,79kg of production or 2.285 head chicken and chicken selling price was Rp16.364/kg. It can be concluded that broiler breeding farms in closed house on the non-partnership model is good and feasible to cultivate. Keywords : Broiler chicken, closed house, non-partnership model, income